PERUBAHAN KONDISI SPASIAL, SOSIAL, DAN BUDAYA KAMPUNG BETAWI CONDET - , MUHAMMAD SYAHPUTRA; , Prof. Ir. Sudaryono, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As a part of history, Kampong Betawi Condet leads to changes that would likely eliminate the identity of a village. Lifestyle changes and modernization of society that generally occur in urban communities, also occurred in Kampong Betawi Condet. It is interesting to be researched how changes in the condition of spatial, social, and cultural communities of the Kampong Betawi Condet as part the development of the city of Jakarta. Researcher concluded that the problems occurred in Kampong Condet is changing of peopleâs mainset in terms of maintaining the Betawi Cultural in Condet Area. The method used in research âChanges Of Spatial, Social, And Cultural Condition In Kampong Betawi Condetâ is Inductive qualitative phenomenology. This method used for finding evidence of changes that occurred in Kampung Betawi Condet since set into the Betawi Cultural Heritage. Change of spatial, social, and cultural happening in Condet is the change that led to the decline. These changes bring the negative influencens in the area of Condet, which are a cultural heritage and a fruit preservation before. Condet which were so fresh, comfortable, and a center by betawi culture now turned into dense settlement and no difference with the other area in Jakarta which has traffic jam, flood problems, and environment pollution. The face of Kampong Betawi Condet which more degraded, indicate that has faded with the Kampong Betawi status.